Mercury Distribution in the Deûle River (Northern France) Measured by the Diffusive Gradients in Thin Films Technique and Conventional Methods - Diviš, Pavel; Kadlecová, Milada; Ouddane, Baghdad (Archives of environmental contamination and toxicology, 2016)
The distribution of mercury in surface water and in sediment from Deûle River in Northern France was studied by application of conventional sampling methods and by diffusive gradients in thin films technique (DGT). Concentration of total dissolved mercury in surface water was 20.8 ± 0.8 ng l(-1). The particulate mercury concentration was 6.2 ± 0.6 µg g(-1). The particulate mercury was accumulated in sediment (9.9 ± 2.3 mg kg(-1)), and it was transformed by methylating bacteria to methylmercury, mainly in the first 2-cm layer of the sediment. Total dissolved concentration of mercury in sediment pore water obtained by application of centrifugation extraction was 17.6 ± 4.1 ng l(-1), and it was comparable with total dissolved pore water mercury concentration measured by DGT probe containing Duolite GT-73 resin gel (18.2 ± 4.3 ng l(-1)), taking the sediment heterogeneity and different principles of the applied methods into account. By application of two DGT probes with different resin gels specific for mercury, it was found that approximately 30% of total dissolved mercury in sediment pore water was present in labile forms easy available for biota. The resolution of mercury DGT depth profiles was 0.5 cm, which allows, unlike conventional techniques, to study the connection of the geochemical cycle of mercury with geochemical cycles of iron and manganese.
Keywords: France; rtuť; Mercury; chemické látky znečišťující vodu; Francie; Water Pollutants, Chemical; Environmental Monitoring; monitorování životního prostředí